Indicators and Dimensions of Clients’ Satisfaction With Veterinary Services Delivery Performance in a Companion Animal Hospital in Accra, Ghana - Paa Kobina Turkson; Celine Naa Dede Coppson; Anthony Joe Turkson (Veterinary Medicine and Science)
ABSTRACT Background Client satisfaction surveys present a chance to find out which services offered by a provider meet or exceed the expectations of clients, and therefore should be maintained, while services that fall short of expectations are identified for improvement. Objectives The aims were to determine if correlations existed between dimensions of service quality (tangibles, reliability, responsiveness, assurance and empathy) and client satisfaction, find out which of 15 selected indicators of service delivery performance were significantly associated with client satisfaction and serve as predictors for satisfaction and determine client satisfaction indices for services rendered at a companion animal hospital. Methods A questionnaire, covering background information and indicators and dimensions of satisfaction, was administered to 208 respondents. Data analyses involved proportions, mean scores, Cronbach reliability test, relative importance indices, correlations, multiple regressions and client satisfaction indices. Results For indicators, the prediction equation was as follows: Overall satisfaction = −44.1 + 15.3 × Drugs availability. For dimensions, the equation was as follows: Overall satisfaction (mean score) = 2.39 + 0.19 × Reliability mean score. The customer satisfaction score was 97.5%, and the mean satisfaction rate was 84.3%. The composite customer satisfaction score was also 84.3%. The customer satisfaction index was 81.5%. Conclusion The study provides, for the first time, attributes considered by clients as contributing to satisfaction with veterinary services delivery for pets in Accra, Ghana. Regression analyses revealed that for dimensions, the reliability mean score, and for indicators, the availability of drugs were the main predictors of overall satisfaction with services delivery. Client satisfaction indices were very high.